Dziedzictwo Solidarności a przebieg transformacji systemowej w Polsce - Brzechczyn, Krzysztof (Wydawnictwo Uniwersytetu Wrocławskiego, 2012)
The aim of this paper is to compare social ideas generated in 1980-1981 by “Solidarność” with results of social transformation in Poland and propose some reasons of discrepancies between the expectations aroused by “Solidarity" in the years l980-1981 and social reality after 1989. the “Solidarność” movement in the years 1980-1981 promulgated its own vision of a “self governed republic” - "the third way of development'' combining ideas from both the right and left of the political spectrum. However, this social vision has been dropped during the years of transformation and replaced by neo-liberalism which has legitimized the course of social change in Poland. There are two main factors responsible for this state of affairs. Firstly, during martial law, “Solidarność” changed from being a revolutionary movement into an elitist reformist movement (especially after 1986) which caused a gradual removal of revolutionary elements from the “Solidarność” program. Secondly, one of the silent conditions of the Round Table compromise was a transformation of the Communist Party apparatus' members into owners with connections to the state. Therefore, the transformation did not lead to the building of democratic capitalism but rather to the creation of an oligarchic system responsible for phenomena such as political clientelism, corruption, and scandals. The idea of a self-governed republic and common good was in contradiction to the interests of oligarchic capitalists, whose social position was based on a violation of such values. This is why the ideas of the “first Solidarność” disappeared from public discourse in Poland in the 1990s.
Keywords: Solidarność; Rzeczpospolita Samorządna; transformacja ustrojowa; uwłaszczenie nomenklatury; oligarchiczny kapitalizm; nie-Marksowski materializm historyczny; neoliberalizm; upadek komunizmu